Zymogenic latency in an ∼250‐million‐year‐old astacin metallopeptidase. Issue 11 (27th October 2022) - Guevara, Tibisay; Rodríguez-Banqueri, Arturo; Stöcker, Walter; Becker-Pauly, Christoph; Gomis-Rüth, F. Xavier
Abstract : The horseshoe crab Limulus polyphemus is an ancient chelicerate that is a model organism for the study of the evolution and function of peptidases. It contains a member of the astacin metallopeptidases, the mechanism of latency of which was revealed by X‐ray structural analysis. Abstract : The horseshoe crab Limulus polyphemus is one of few extant Limulus species, which date back to ∼250 million years ago under the conservation of a common Bauplan documented by fossil records. It possesses the only proteolytic blood‐coagulation and innate immunity system outside vertebrates and is a model organism for the study of the evolution and function of peptidases. The astacins are a family of metallopeptidases that share a central ∼200‐residue catalytic domain (CD), which is found in >1000 species across holozoans and, sporadically, bacteria. Here, the zymogen of an astacin from L. polyphemus was crystallized and its structure was solved. A 34‐residue, mostly unstructured pro‐peptide (PP) traverses, and thus blocks, the active‐site cleft of the CD in the opposite direction to a substrate. A central `PP motif' (F 35 ‐E‐G‐D‐I 39 ) adopts a loop structure which positions Asp38 to bind the catalytic metal, replacing the solvent molecule required for catalysis in the mature enzyme according to an `aspartate‐switch' mechanism. Maturation cleavage of the PP liberates the cleft and causes the rearrangement of an `activation segment'. Moreover, the mature N‐terminus is repositioned to penetrate the CD moiety and is anchored to a buried `family‐specific' glutamate. Overall, this mechanism of latency is reminiscent of that of the other three astacins with known zymogenic and mature structures, namely crayfish astacin, human meprin β and bacterial myroilysin, but each shows specific structural characteristics. Remarkably, myroilysin lacks the PP motif and employs a cysteine instead of the aspartate to block the catalytic metal.